Older people in the structure of local society - results and experiences of the panel survey in Nyíregyháza - Mihály, (Magyar Gerontológia, 2025)
The aim of the presentation is to explore the situation of the elderly based on the results of an urban panel study. The lecture examines the position of older people in local society in three areas: their distribution across income strata representing positions in the social structure, the possibility of precarity among the elderly, and their subjective health status.